Maniac Magee / a novel - Spinelli, Jerry (New York : Little,Brown, 1990)
After his parents die, Jeffrey Lionel Magee's life becomes legendary, as he accomplishes athletic and other feats which awe his contemporaries.
Keywords: Athletes -- Fiction; Orphans -- Fiction; Newbery Medal; Legends -- Fiction